Insect Management for Okra - Susan E. Webb (EDIS)
This document is ENY-466 (which replaces ENY-434), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002. Revised: July 2003.